Ancient Greek Personal Names. Part II: A View from Aristophanes’ Acharnians - Szefliński, Waldemar (Sensus Historiae, 2021)
The article is a ‘case study’ of Aristophanic anthroponymy. The subject matter was introduced in the author’s previous Sensus Historiae text titled ‘Ancient Greek Personal Names. Part I: Theory.’ The current article is an overview of Ancient Greek personal names to be found in Aristophanes’ comedy Acharnians listed along the taxonomic lines delineated in the previous text. Each name is accompanied with a morphological analysis whereby its semantic content is established. This allows the author to group the Aristophanic personal names into two categories, that is, names comically neutral and names comically marked, and exemplify the latter category with name-forms extracted from (most of) the translations of the comedy Acharnians into English. The author also offers a comment on the usefulness of the above-mentioned classification of Aristophanes’ anthroponyms.